2013
DOI: 10.1002/14651858.cd002808.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Depot versus daily administration of gonadotrophin-releasing hormone agonist protocols for pituitary down regulation in assisted reproduction cycles

Abstract: Depot versus daily administration of gonadotrophin-releasing hormone agonist protocols for pituitary down regulation in assisted reproduction cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 47 publications
3
27
0
3
Order By: Relevance
“…The most effective form of agonist protocol remains controversial. In 2013, a meta‐analysis study showed that it was not clear which one was the better protocol for pituitary desensitization in IVF cycles . This retrospective analysis aimed to compare the use of the short‐ and long‐acting long protocols with IVF cycles to study the effectiveness and safety of the two protocols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most effective form of agonist protocol remains controversial. In 2013, a meta‐analysis study showed that it was not clear which one was the better protocol for pituitary desensitization in IVF cycles . This retrospective analysis aimed to compare the use of the short‐ and long‐acting long protocols with IVF cycles to study the effectiveness and safety of the two protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the level of LH could improve the oocyte development by increasing the estrogen/androgen ratio 4 ; moreover, it would improve the endometrial receptivity and wide implantation window. [5][6][7][8] A Cochrane review showed that the long protocol was associated with the best clinical pregnancy rate among the variety of controlled ovarian hyperstimulation (COH) protocols, 9 and was recommended by the National Institute for Health and Care Excellence. The long protocol has two forms: the long-acting and short-acting long protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews (e.g. from the Cochrane collaboration) are regularly issued in order to compare different protocols but often fail to demonstrate the purported superiority of the new approaches (3,4,5,6). On the other hand, new protocols of infertility treatment and ART are greatly needed, especially considering the constantly increasing age of women in couples undergoing ART (7), a factor which decreases the efficacy of the treatment by affecting both pregnancy and abortion rate.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to optimize protocols for controlled ovarian stimulation to provide adequate numbers of good-quality oocytes, which is the cornerstone of assisted reproductive techniques. The Cochrane Database of Systematic Reviews is regularly published to compare different protocols but often fail to demonstrate the purported superiority of the new approaches [35][36][37][38]. However, to be able to successfully achieve this, an ORT needs to have a high specificity and predictive value, as well as reproducibility [34].…”
Section: Discussionmentioning
confidence: 99%